Breast cancer in a multi-ethnic Asian setting: results from the Singapore-Malaysia hospital-based breast cancer registry - Pathy, Nirmala Bhoo; Yip, Cheng Har; Mohd Taib, Nur Aishah; Hartman, Mikael; Saxena, Nakul; Iau, Philip; Bulgiba, Awang; Lee, Soo Chin; Lim, S.E.; Wong, John E.L.; Verkooijen, Helena M. (Elsevier, 2011)
Two hospital-based breast cancer databases (University Malaya Medical Center, Malaysia n = 1513 and National University Hospital, Singapore n = 2545) were merged into a regional registry of breast cancer patients diagnosed between 1990 and 2007. A review of the data found 51% of patients diagnosed before the age of 50 years. and 72% percent of the women were Chinese followed by Malays (16%), Indians (8%), and other races (4%). Median tumor size at presentation was 26 mm and about 25% of patients presented with TNM stage III or IV disease. Most tumors were of ductal histology (87%). Fifty-seven percent of tumors were estrogen receptor positive and 40% were poorly differentiated. Of those patients who had surgery, 70% had mastectomy while 30% had breast conserving surgery. Overall, chemotherapy was administered to 56% of patients and hormonal treatment to 60%. Five-year overall survival was 82.5% in patients with TNM stage 0 to stage II cancer, and 30.2% in those with later stages. (C) 2011 Elsevier Ltd. All rights reserved.